INTEGRASI-INTERKONEKSI KEILMUAN PROF. AMIN ABDULLAH: KESALINGTERKAITAN ANTARA ILMU-ILMU AGAMA DAN SCIENCE - Febri Hijroh Mukhlis (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2018)
Islam and science have such a historical bonding. Both of them are an important part in the dynamics of global civilization. Today, when humanities’ problem is going more complex, Islam cannot speak with only a face or with a mono scientific discipline. Islamic scholarship should interact to developing modern sciences. In this modern era, people have to think multidisciplinary, not linear. Amin Abdullah’s idea on integrative-interconnective paradigm is an excellent effort in developing religious thought and sciences altogether. His idea has an important point in suggesting that all scientific disciplines should interact each other, to respond the dynamics of civilization that continuously growing.